MACKEREL FISHERY OF KARWAR - Pradhan, L B (Indian Journal of Fisheries, 2015)
Karwar (Lat. 14Â° 50' N and Long. 74Â° 03' E, North Kanara, Bombay State) is one of the major mackerel fishing centres of India. The Kanara Coast, which is 76 miles long, runs in a straight line except for the shallow Karwar and BeUkeri bays in the north. The coast-line extending from Majali, on the southern boundary of Goa to Bhatkal, the southernmost limit of Bombay State, is of a varied character with rocky islands and capes, stretches of sandy beach and narrow river mouths.